Reflections on the Yoruba Past: Toyin Falola on Isaac Delano - Wale Oyedeji (Yoruba Studies Review)
Toyin Falola remains one of the most illuminating voices with remarkable efforts to reposition the continent of Africa on the appropriate place on the global map. He has provided sufficient evidence that he deserves the accolades he attracts from contemporaries and admirers. More than many of his contemporaries, Toyin Falola continues to demonstrate that knowledge production from Africa is sustainable if past events are interrogated accordingly. In very many ways, he displays quality content that gives him the sort of image he has built for Africans generally, and himself particularly in the world of intellectualism. The debate about the essentialism of African knowledge economy, especially the Yoruba culture, is centuries old, and frozen in its condition. It became prominently popular from the beginning of African’s contact with Europeans and Arabs, and this, ever since then, has attracted deepened engagement by African scholars whose primary intention was to defend their cultural legacy.